High-Tech Sector in the Benelux Countries Compared to the Remainder of the European Union – A Taxonomic Analysis - Joanna M. SZAREK (Communications of International Proceedings, 2021)
The development of new technologies and artificial intelligence is noticeable above all at regional level. The accumulation in a given region of such elements as scientific and research facilities, logistics infrastructure, and high-quality human capital, as well as the openness of regional authorities to implement innovations and make the transformation towards a knowledge-based economy is fundamental to successfully building a competitive position in a quasi-national arena. The purpose of this article is to show regional differences in the level of the high-tech sector in Benelux compared to other states of the European Union, by using selected taxonomic methods. By creating a ranking of states according to the standardized sum index, it was possible to indicate the dominant group of countries in this area, which included: Germany and the Czech Republic. Of the Benelux countries, the best position in the ranking was obtained by the Netherlands which qualified for the third category of states, while the worst score in the region went to Luxembourg which placed in the fifth and last group of Member States with the lowest degree of advancement in the high-tech sector.
Keywords: Regional Development; Benelux; Knowledge-Based Economy; High-Tech Sector.